Aesthetic-Therapeutic Applications and Physiological Effects of Cryofrequency - Valton da Silva Costa; Tatiana Catarina Alburquerque Clementino dos Santos (Journal of Novel Physiotherapy and Physical Rehabilitation - Peertechz Publications, 2020)
Introduction: Cryofrequency is a non-abrasive and non-invasive aesthetic treatment method aimed at complaints related to localized adiposity and cutaneous flaccidity. The method consists of the generation of radiofrequency waves that in contact with the subcutaneous tissues produce heat. The differential of the cryofrequency is that this method uses a system of superficial cooling, producing a thermal shock by combining deep heat and superficial cold. Aim: To understand the aesthetic-therapeutic and physiological effects of the cryofrequency method. Method: This study is a bibliographical review. Thus, a search for specialized literature was made and the results were presented descriptively. Results and discussion: The main aesthetic-therapeutic applications observed in the gathered studies are the reduction of flaccidity and body fat content. The main physiological effects are the shortening of collagen fibers, the production of new collagen fibers, and the death of adipocytes due to necrosis and apoptosis, both due to the effect of heat on the subcutaneous tissue. Conclusions: We conclude that there is a good level of evidence regarding the use of cryofrequency, though studies of higher methodological quality are necessary to reduce the biases arising from the different types of equipment used and the subjectivity of the measures of outcomes adopted in the carried-out studies.